2021
DOI: 10.3390/f12030287
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Growth and Log Quality of Douglas-Fir (Pseudotsuga menziesii (Mirb.) Franco) Provenances

Abstract: Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) is a non-native conifer from western North America that was introduced into European forests at the end of the 19th century. Plantations of Douglas-fir in Europe have shown good performance, quality, and resilience to exacerbating climatic conditions. However, all these qualities strongly depend on provenance. A total of 1061 surviving trees of fifteen different Douglas-fir provenances were measured in a Slovenian provenance trial that was established within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…However, it also grows at lower (200 m asl) and higher elevations (up to 1300 m asl in Slovakia and 1600 m asl in France; Coopérative Forestière Bois Limousin 2016), but with lower yields. The best climatic conditions for growing Douglas-fir in Europe are in moderate to moist temperate climates, with mean annual temperatures of 7 − 8 ºC (Czech Republic: Mondek and Balaš 2019), 7 − 9 ºC (Romania: Stănescu et al 1997), 8 − 11 ºC (France: Coopérative Forestière Bois Limousin 2016), 9 − 11 ºC (Slovenia: Čater 2021Smolnikar et al 2021). The most important limiting factor for successful cultivation of the species in Europe is the minimum mean annual precipitation, with a critical lower threshold between 600 mm (Czech Republic: Mondek and Balaš 2019;Romania: Haralamb 1967;Slovakia: Slávik pers.comm.…”
Section: Site and Climatementioning
confidence: 99%
See 1 more Smart Citation
“…However, it also grows at lower (200 m asl) and higher elevations (up to 1300 m asl in Slovakia and 1600 m asl in France; Coopérative Forestière Bois Limousin 2016), but with lower yields. The best climatic conditions for growing Douglas-fir in Europe are in moderate to moist temperate climates, with mean annual temperatures of 7 − 8 ºC (Czech Republic: Mondek and Balaš 2019), 7 − 9 ºC (Romania: Stănescu et al 1997), 8 − 11 ºC (France: Coopérative Forestière Bois Limousin 2016), 9 − 11 ºC (Slovenia: Čater 2021Smolnikar et al 2021). The most important limiting factor for successful cultivation of the species in Europe is the minimum mean annual precipitation, with a critical lower threshold between 600 mm (Czech Republic: Mondek and Balaš 2019;Romania: Haralamb 1967;Slovakia: Slávik pers.comm.…”
Section: Site and Climatementioning
confidence: 99%
“…There is consensus that self pruning of Douglas-fir is slow, even in dense stands (Fig. 2) (e.g., Hermann and Lavender 1990;Hubert and Courraud 1998;Lowell et al 2014;Drewett 2015;, so unpruned Douglas-fir can be very knotty (Haralamb 1967;Smolnikar et al 2021).…”
Section: Thinning and Pruningmentioning
confidence: 99%
“…Orlić and Ocvirek (1994), Perić et al (2009Perić et al ( , 2011, Orlić and Perić (2015) found statistically significant differences among provenances in provenance tests in Croatia. Smolnikar et al (2021), in research of fifteen Douglas fir provenances in the IUFRO provenance test established in 1966/67 in Slovenia, found significant differences among provenances in terms of survival rate, growth, and quality. They also found a positive and significant correlation between tree height in 1985 and average diameters measured in 2017.…”
Section: Discussion and Conclusion -Diskusija I Zaključcimentioning
confidence: 97%
“…It has clearly shown good adaptability under challenging conditions, e.g., resistance to ice storms, drought and bark beetle infestation in areas where Norway spruce was severely affected, as well as good growth performance. For this reason, Douglas fir has currently considered the most promising non-native tree species in Slovenian forests ( Smolnikar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%